Mechanical properties and thermal stability of rPET/HDPE plastic composite - Nik Ruqiyah, Nik Hassan (2020)
Nowadays, the large amount of waste plastic bottles in landfills has become a major global environmental issue. This issue occur because the industry plastic production produce plastic continuously. lt is well known that one of the possible methods for recycling these plastic bottles is to process them for use as raw materials or reinforced polymer plastic. However, recycled plastic bottles are rarely used because the mechanical properties of the recycled materials would decrease due to the degradation and decomposition of the polymer during recycle process which effect the mechanical and thermal properties. In this research, recycled polyethylene terephthalate (rPET) were used as a reinforcement in a high-density polyethylene (HOPE) matrix. The aim of the study is to fabricate rPET/HOPE composites with enhanced mechanical properties, and also to investigate the effect of the rPET filler loading and maleic anhydride grafted polyethylene (MAPE) coupling agent on the rPET/HOPE composite. The lab work started by hot pressing the mixture of rPET and HOPE using hot pressing machine to produce rPETtHOPE composite at different rPET filler loading of I 0%, 30%, and 50%, respectively. Samples of rPET!HOPE composite with the addition of 5% and 10% of MAPE were also prepared in this study. The samples of rPET/HOPE composite were divided into three main types, namely Type I, Type II and Type Ill which refer to rPETIHOPE/O%MAPE, rPET/HOPE/5%MAPE and rPET/HOPE/10%MAPE. Additionally, Code A, B, and C were assigned referring to the percentage ofrPET filler loading, which are I 0%, 30%, and 50%, respectively . Overall, there are nine samples of composite prepared which labelled as lA, IB, IC, IIA, liB, IIC, IliA, liB, IIIC in each batch. The tensile properties of the rPET !HOPE composites were tested by Universal Testing Machine. While, thermal stability were tested by using Thermo-Gravimetric Analysis (TGA).Other than that, analysis on the morphology of the tensile fractured surface was done using Scanning Electron Microscope (SEM), while Fourier Transform Infrared Spectroscopy (FTIR) was used to analyze the influence ofMAPE in enhancing interfacial bonding of the rPETIHOPE composite. From the experimental result, the mechanical properties of rPET/HDPE/MAPE composite has been improved with the highest tensile strength of 156.270 MPa was observed in a specimen with 10% rPET/HDPE/10%MAPE (Type IliA). Meanwhile, the thermal stability of the rPET/HDPE composites \Vith the addition of MAPE, Type II and Type III composites were decreased if compared to pure HOPE and Type I composite. This might be due to the broken chains in the polymers that resulted from the interactions between the anhydride groups of the maleated coupling agent and the hydroxyl groups (-OH) of the rPET. Overall, from the analysis, it was demonstrated that the mechanical properties of the rPET/HOPE composite were improved with the addition of the MAPE coupling agent but at the same time reduced its thermal stability. From this research, new information obtained can encourage other researchers to possibly used recycled material such as rPET as a reinforcement in the composite materials. The rPET/HDPE composite could be useful as packaging materials in plastic packaging industry.